PENGARUH STRATEGI PEMASARAN TERHADAP VOLUME PENJUALAN KRUPUK PADA UD. SUBANDI ROGOJAMPI DI KABUPATEN BANYUWANGI - Arif Saefulloh; Ika Wahyuni (Growth, 2011)
The purpose of this study was to determine the effect of Marketing Strategy on Krupuk Sales Volume at UD. SUBANDI Rogojampi in Banyuwangi Regency. The population in this study were all UD SUBANDI employees, (starting from expert staff and its divisions) in the UD SUBANDI companyRogojampi and UD. SUBANDIconsumers. There are 2 (two) variables in this study, namely variable (X) is a marketing strategy, Variable (Y) is sales volume. In this study using data collection methods through questionnaires, documentation. Based on the results of the study, it can be concluded: simple regression calculation results obtained from the correlation coefficient between marketing strategies on sales volume, r value of 0.31 which indicates a strong relationship between the effect of marketing strategies on sales volume. Regression coefficient of 0.43. This is a contribution of marketing strategy variables to sales volume. So that it can be concluded that there is an influence of marketing strategies on sales volume.